Exploring School Management Strategies on Alternatives to Corporal Punishment for Managing Student Aggression in Arusha, Tanzania - Mshai, Reuben; Nemes, Joyce; Bwagilo, Huruma Olofea (International Journal of Global Community, 2026)
In many African countries, including Tanzania, children often experience immediate physical punishment from parents or caregivers after misbehaving, a practice that extends into schools where students can be caned with permission from the educational authorities. The reliance on corporal punishment, highlights the urgent need for effective, non-violent strategies to manage student misbehaviour, particularly aggression, thus fostering a safer and more supportive educational environment. This qualitative study, aimed at exploring alternative strategies employed by school managements in order to handle students’ aggression. It was grounded on the Social Learning Theory and Attachment Theory. Besides, the study employed the multiple-embedded case study design coupled with purposive sampling technique and snowball sampling technique along with the semi-structured interview, focus group discussion and documentary review as data collection methods. Subsequently, the study identified five key strategies namely creating conducive environments that foster security and support, establishing mentorship programmes that provide behavioural models and emotional support, changing teachers’ mind-sets so as to promote non-violent conflict resolution, making sure issues concerning student behaviours are discussed during parent-teacher meetings in order to make students align with behavioural expectations and enhancing religious teachings which will provide ethical frameworks and emotional guidance. These strategies align with both Social Learning Theory and Attachment Theory which encourage positive behaviour modelling and establishing secure emotional bonds respectively. The research underscores the necessity for comprehensive support systems which address both behavioural and emotional needs of students to effectively reduce aggression. Furthermore, it is recommended that, school managements should adopt these strategies as a framework for managing students’ aggression, moving away from reliance on corporal punishment.